THE Symbolism of the Extinction of the Senate in the Project of the New Chilean Constitution - Vilas Boas Marques Bueno e Lopes, Alexandre Tomaz; Santander, Carlos Ugo (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2024)
The purpose of this article is to present the historical, social and legal aspects capable of demonstrating the symbolism in the extinction of the Senate in the reconfiguration of the political system foreseen in the rejected project of the new Chilean constitution, since such a document is an inseparable part of the trajectory of the ongoing constitutional movement in Chile. The analysis of these aspects will allow understanding how the struggles of groups and social movements, throughout history, led to the Constitutional Convention incorporating this change and how it can be interpreted in view of the human rights of access and democratic participation in political power.